In vitro and in vivo anthelmintic activity of extracts from Artemisia parviflora and A-sieversiana - Irum, S.; Ahmed, H.; Mirza, B.; Donskow-Lysoniewska, K.; Muhammad, A.; Qayyum, M.; Simsek, S. (Walter de Gruyter Gmbh, 2017)
In the northern areas of Pakistan, the use of Artemisia based therapeutics is a common practice. Plants of genus Artemisia are known to possess anthelmintic and therapeutic effect. Infections caused by gastrointestinal nematodes are major threat to livestock industry across the world resulting in loss of production and indirect economic losses due to high cost of anthelmintic drugs. Present study was carried out to evaluate in vitro and in vivo effect of Artemisia sieversiana and Artemisia parviflora on Haemonchus contortus, a parasitic nematode of small ruminants. Methanolic plant extract was tested against three different developmental stages using an egg hatch assay, infective larvae and adult worm motility assay. Different concentrations were used for the bioassays and post exposure mortality was recorded after 8 hr for adult worms and infective larvae, while egg inhibition percentage was observed after 27 hr. A highly significant ability to inhibit the egg hatching (100 %) was recorded for both plant extracts while, the highest activity for adult worm assay and larvicidal assay was 90 % for A. sieversiana. The highest activity for adult motility and larvicidal assay for A. parviflora was 89 % and 86.6 % respectively. For in vivo trials maximum parentage reduction was 77.0 % for A. sieversiana and 73.6 % for A. parviflora. It is concluded that selected plant extracts were effective in reducing worm burden in animals.
Keywords: Artemisia parviflora; Artemisia sieversiana; plants; Anthelmintics; Haemonchus contortus